Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.22159/ajpcr.2020.v13i5.37909
|View full text |Cite
|
Sign up to set email alerts
|

Β-SITOSTEROL: ISOLATION FROM MUNTINGIA CALABURA LINN BARK EXTRACT, STRUCTURAL ELUCIDATION AND MOLECULAR DOCKING STUDIES AS POTENTIAL INHIBITOR OF SARS-CoV-2 Mpro (COVID-19)

Abstract: Objecive: A novel human coronavirus (HCoV), labelled as SARS-CoV-2 (COVID-19), causing pneumonia is spreading around the world. At present, there are no specific treatments for COVID-19. β-sitosterol is well known for its multiple biological actions. The aim of this research is to isolate and study binding affinity of β-sitosterol for SARS-CoV-2 (COVID-19) main protease (Mpro). Methods: Extraction and Column chromatography was performed to isolate the β-sitosterol from n-hexane extract of Muntingia calab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 11 publications
(14 reference statements)
0
27
0
Order By: Relevance
“…The active amino acid residues in the protein were identified and noted using BIOVIA Discovery Studio Visualizer (version-19.1.0.18287) [36]. The complete docking procedure along with ligand preparation and target preparation have been performed as described in the reference article [1]. The recently elucidated structure pre-fusion 2019-nCoV (SARS-CoV-2) spike glycoprotein with a single receptor-binding domain up was obtained from the RCSB Protein Data Bank (PDB ID: 6VSB) which was released on 26 February 2020 (https://www.rcsb.…”
Section: Molecular Docking Studies Of β-Sitosterol With Rbd Of Sars-cov-2 Spike Glycoproteinmentioning
confidence: 99%
See 1 more Smart Citation
“…The active amino acid residues in the protein were identified and noted using BIOVIA Discovery Studio Visualizer (version-19.1.0.18287) [36]. The complete docking procedure along with ligand preparation and target preparation have been performed as described in the reference article [1]. The recently elucidated structure pre-fusion 2019-nCoV (SARS-CoV-2) spike glycoprotein with a single receptor-binding domain up was obtained from the RCSB Protein Data Bank (PDB ID: 6VSB) which was released on 26 February 2020 (https://www.rcsb.…”
Section: Molecular Docking Studies Of β-Sitosterol With Rbd Of Sars-cov-2 Spike Glycoproteinmentioning
confidence: 99%
“…This article is an extension to our recently published article in Asian Journal of Pharmaceutical and Clinical Research, entitled "Β-Sitosterol: Isolation from Muntingia Calabura Linn. Bark Extract, Structural Elucidation, and Molecular Docking Studies as Potential Inhibitor of SARS-CoV-2 M pro (COVID-19)" [1]. The article describes detailed procedure for the isolation (by Column Chromatography) and structural characterization (by FTIR, UV-Visible Spectroscopy and HPTLC) of β-sitosterol from Muntingia Calabura bark.…”
Section: Introductionmentioning
confidence: 99%
“…The crystal structure of 6VSB did not indicate a native ligand. Molecular docking proceeded as described [ [43] , [44] , [45] ] . The interacting amino acid residues in the protein were identified using BIOVIA Discovery Studio Visualizer version 19.1.0.18287 (Dassault Systemes, Paris, France) [ 46 ] .…”
Section: Methodsmentioning
confidence: 99%
“…β-Sitosterol is well known for its multiple biological actions and is isolated from n-hexane extract of the M. calabura bark for phytochemical analysis. β-Sitosterol has stronger binding affinity for SARS-CoV-2 Mpro than favipirapir as it interacts with greater number of amino acids and forms more Van-der-waal forces with target molecule (42). In silico analysis demonstrated that the terpenoids bonducellpin D, caesalmin B and the flavonoid 5,7-dimethoxyflavanone-40 -O-beta-d-glucopyranoside have promising binding affinity with Mpro of SARS-CoV-1, SARS-CoV-2 and MERS-CoV with potential values compared with repurposed drugs (43).Other natural metabolites capable of inhibiting the Mpro of SARS-CoV-2 in molecular docking are kaempferol, quercetin, luteolin-7-glucoside, demethoxycurcumin, naringenin, apigenin,7-glucoside, oleuropein, catechin, curcumin, and epigallocatechin.…”
Section: Mpromentioning
confidence: 99%